Fasakh Perkawinan Karena Suami Impoten Perspektif Imam al-Syafi’i dan Undang¬-Undang Perkawinan - Azis, Muhammad; Qayyum, Abd. Rahman (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2022)
This journal discusses the Fasakh of Marriage Due to Impotent Husbands according to Imam Syafi'I and the Marriage Act. Fasakh is something that is allowed in Islamic law, but how is the law of marriage because the husband is impotent if it is seen according to Imam Syafi'i and the marriage law and how is the relevance between the two laws. This research is a library research that aims to analyze the views of Imam Syafi'i and the Marriage Law regarding the marriage phase because the husband is impotent. In this study, the authors use a normative-juridical approach, namely an approach with the aim of discovering legal doctrines or principles relating to marriage marriages, so that they are expected to be able to clearly analyze the views of Imam Syafi'i and the Marriage Law regarding marriage marriages because impotent husband with data collection techniques through a review of library materials related to the problem. Based on the results of the study, based on the opinion of the Imam Shafi'I school (fiqh munakahat) if the husband is impotent and his impotence results in the purpose of marriage being not achieved, either for procreation or for having sexual relations and causing suffering for his wife, the wife has the right to sue Faskh and the judge may validate the marriage if it is proven. Meanwhile, in the Marriage Law regarding the concept of marriage because the husband is impotent, it is explained in Article 22 of Law Number 1 of 1974 concerning marriage, that: "a marriage can be annulled if the parties do not meet the requirements to enter into a marriage". The conditions referred to are described in more detail in Article 19 letter (e) of Government Regulation Number 9 of 1975 concerning divorce can occur for reasons, namely that one of the parties has a disability or illness which results in not being able to carry out his obligations as a husband. However, the Marriage Law does not regulate in detail the diseases that can be submitted as reasons for divorce. The benchmark is where the disability or disease interferes with the parties carrying out their obligations as husband and wife, then the disability or disease can be submitted as a reason for divorce. the impossibility of carrying out the obligations required in Article PP No. 9 of 1975 Article 19 Letter (e) is an impotent disease that is permanent or for a long time. The relevance between the Munakahat Fiqh and the Marriage Law regarding the marriage phase because the husband is impotent is the existence of a relationship that explains and complements each other